A prospective, randomized, controlled trial comparing the outpatient treatment of pediatric and adult partial-thickness burns with Suprathel or Mepilex Ag - Hundeshagen, Gabriel (Journal of burn care & research, 2018)
Abstract: Modern treatment of partial-thickness burns follows the paradigm of less frequent dressing changes to allow for undisturbed reepithelialization of the burn wound. We compared Mepilex Ag (M), a silver-impregnated foam dressing, and Suprathel (S), a DL-lactid acid polymer, in the outpatient treatment of partial-thickness burns in pediatric and adult patients. Patients were enrolled in a randomized, controlled, prospective clinical trial. We monitored time to reepithelialization, wound pain, discomfort during dressing changes, and treatment cost. Objective scar characteristics (elasticity, transepidermal water loss, hydration, and pigmentation) and subjective assessments (Patient and Observer Scar Assessment Scale) were measured at 1 month post burn. Data are presented as mean ± SEM, and significance was accepted at P < 0.05. Sixty-two patients (S n = 32; M n = 30) were enrolled; age, sex, and burn size were comparable between the groups. Time to reepithelialization was not different between the groups (12 days; P = 0.75). Pain ratings were significantly reduced during the first 5 days after burn in the Suprathel group in all patients (P = 0.03) and a pediatric subgroup (P < 0.001). Viscolelasticity of burned skin was elevated compared with unburned skin in the Mepilex Ag group at 1 month post burn. Patients treated with Suprathel reported better overall scar quality (S: 2; M: 4.5; P < 0.001). The cost of treatment per square centimeter for Mepilex Ag was considerably lower than that of Suprathel. Both dressings are feasible and efficacious for the outpatient treatment of minor and selected moderate partial-thickness burns. Reduced pain, especially in a pediatric patient population, may be advantageous, despite increased treatment cost.